STUDY OF THE PREVALENCE OF SAGUN BHAKTI IN BHAKTIKAL LITERATURE - Kamlesh Kumar; Mishra, Shrikant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sagun Bhakti is a process of seeing God everywhere. When the devotee starts seeing his deity in every particle, then his sadhana is successful. Those who speed up their sadhana with the basic mantra of 'Hari Vyapak Sarvatra Samana' are Sagun worshippers. Sagun worshipers believe that whoever is endowed with qualities is Sagun and Nirgun in which qualities cannot be imposed. All the poets of Bhaktikal, no matter which poetic stream they represent, can definitely see some form of Sagun Bhakti in all of them. Every poet of Ram poetry stream does Sagun Bhakti of Purna Brahma Ram. Their entire literature is soaked in the worship of Ram. In the Krishna Bhakti stream, the tradition of worshiping Krishna in the form of Brahma is widespread. In Nirguna branch, many qualities of Saguna devotion like love and remembrance are found in Gyanashrayi and Premashrayi poetry streams also. Whose pursuit is the theme of the presented research paper.